Digital teaching competence: a growing need in the context of the COVID-19 pandemic - John Barja-Ore; Lupe Y. Gallardo-Pastor (Revista Cubana de Medicina Militar)
Digital teaching competence: a growing need in the context of the COVID-19 pandemic